On the Compilation of a Textbook in French for Students of Non-Linguistic Universities - Tamara, Kavilova (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the problem of developing a professionally oriented textbook on the French language as a second foreign language for the initial stage of training on the example of the experience of the Jizzakh State Pedagogical Institute. The task is to design and create conditions that allow students studying in a non-linguistic university to acquire communicative competence for verbal and written communication in a foreign language to solve problems of interpersonal and intercultural interaction. The principles, specificity and difficulties of organizing the process of teaching French as a second foreign language after English are studied. The goals, principles, methods and techniques of professionally oriented training in the main types of speech activity are considered. The components of foreign language communicative competence, its specificity in relation to the sphere of professional activity are noted. Particular attention is paid to the selection of the content of the developed training manual. It is concluded that in order to develop an effective textbook, it is necessary to take into account the future specialty of students, their professional motivation, level of knowledge of a foreign language, features of a second foreign language and the specifics of the development of foreign language communicative competence in the professional field.